A novel fish cell line derived from the brain of Chinese perch Siniperca chuatsi: development and characterization. Issue 1 (6th November 2014) - Fu, X.; Li, N.; Lai, Y.; Luo, X.; Wang, Y.; Shi, C.; Huang, Z.; Wu, S.; Su, J.
<x xml:space="preserve">Abstract</x> In this study, a continuous cell line (named as CPB) was established from Siniperca chuatsi brain and has been subcultured >140 times. CPB cell line predominantly consisted of fibroblast‐like cells that could grow better in Leibovitz's L‐15 supplemented with 10% foetal bovine serum at 28° C. Polymerase chain reaction amplification of 18s recombinant (r)RNA confirmed the origin of this cell line from S. chuatsi. The CPB cell line was cryopreserved at different passage levels and revived successfully with 80–90% survival. The cell line was further characterized by chromosome number and transfection. The CPB cells were highly susceptible to infectious spleen and kidney necrosis virus (ISKNV) with a titre of 6·58–6·62 log TCID50 ml−1 and numerous ISKNV particles were observed in the cytoplasm by transmission electron microscopy. At the same time, ISKNV infection was confirmed by reverse transcriptase polymerase chain reaction, immunodot blot and individual challenge experiments. The development and characterization of a new brain cell line from S. chuatsi were described in this study and it could be used as an in vitro tool for propagation of ISKNV and gene expression studies.